827 The Use of High Resolution Ultrasound in the Evaluation of Traumatic Peripheral Nerve Injury: A Systematic Literature Review. (April 2023) - Braverman, Aaron; Shi, Shi; Herring, Eric; Labak, Collin; Azghadi, Adel; Preston, David; Miller, Jonathan
Abstract : INTRODUCTION: Traumatic peripheral nerve injury (TPNI) represents a heterogeneous pathology with potential for severe disability. High-resolution ultrasound (HRU) has potential as a non-invasive diagnostic tool to assess injury and inform management decisions, potentially at an earlier time point than traditional electrodiagnostic testing. Standardized assessment of TPNI using HRU is not available in the current literature. We aimed to evaluate the effectiveness of pre-operative HRU in the setting of TPNI through a literature review. METHODS: A systematic literature review was performed adhering to PRISMA guidelines, yielding 84 articles for review. Inclusion criteria included papers that examined ballistic, sharp, and avulsion etiologies of TPNI, and that used ultrasound for initial evaluation of the TPNI. Exclusion criteria included papers with primarily pediatric patients, reviews, meta-analyses, papers not in English, and papers that focused on iatrogenic PNIs. RESULTS: 48 studies met inclusion and exclusion criteria, including 19 case studies, 8 retrospective studies, and 19 prospective studies describing 569 total patients who experienced TPNI. Mean age was 33 years. The studies characterized 121 median, 97 ulnar, 141 radial, and 222 other TPNI from 24 ballistic, 231 sharp, 78 avulsion, and 13 unspecified injuries. The most common HRU findings preoperatively were neuroma formation (79), fascicular swelling (141), and complete discontinuity of epineurium (155). The timing of HRU after TPNI was variable with 37% and 41% of patients undergoing HRU within 6 weeks after TPNI versus more than 6 weeks after TPNI respectively. CONCLUSIONS: HRU is a promising clinical tool for the evaluation of TPNI. Further work is needed to define the appropriate timing for when HRU can be used to evaluate TPNI, as well as radiographic findings that may be clinically relevant in operative evaluations.